Structural, elastic, electronic, magnetic and thermal properties of X3FeO4 (X = mg, ca and Sr) materials - Mohammed El Amine Monir; Abdelkarim Bendoukha Reguig; M. A. Ghebouli; K. Bouferrache; Faisal Katib Alanazi; M. Fatmi; H. Bouandas (Scientific Reports, 2025)
Abstract This prediction evaluates the different physical characteristics of magnetic materials X3FeO4 (X = Mg, Ca and Sr) by using density functional theory (DFT). The generalized gradient approximation (GGA) approach is chosen to define the exchange and correlation potential. The structural study of the compounds X3FeO4 (X = Mg, Ca and Sr) shows that the ferromagnetic phase is the more stable ground state, where all the parameters of the network are given at equilibrium. The calculated elastic constants confirm their stability in the cubic structure. The electronic characteristics calculated using the GGA and GGA + U approaches prove that all these compounds are semi-metallic with a wide band gap (EHM) and a high Curie temperature (TC). Furthermore, the magnetic moments of the studied compounds are calculated in order to claim their half-metallicity behavior. The p-d hybridization between the 3d-Fe and 2p-O states generates weak magnetic moments in the non-magnetic X and O sites, and decreases the Fe atomic moment relative to its free space charge of 4 µB. The thermal parameters including the thermal expansion coefficient, the heat capacity at constant volume and the Debye temperature were calculated for these compounds.